1988
DOI: 10.1093/oxfordjournals.humrep.a136783
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of living human oocytes: cellular basis and developmental consequences of perturbations in chromosomal organization and complement

Abstract: Chromosome complement and location were examined by fluorescence microscopy for 225 meiotically mature (metaphase II) human oocytes after staining with DNA-specific probes. Both preovulatory oocytes and oocytes that failed to fertilize in vitro were analysed. After inspection in the living state, oocytes were selected for karyotyping or transmission electron microscopy. The findings demonstrate a high correlation between assessments of chromosome complement in living oocytes and the results from subsequent kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…It has been suggested that the dysmorphic phenotypes observed during stimulated cycles might reflect a high frequency of aneuploidy related to ovarian stimulation (7). However, in this case results from karyotype analyses of the fetuses in both pregnancies were normal.…”
Section: Discussionmentioning
confidence: 53%
“…It has been suggested that the dysmorphic phenotypes observed during stimulated cycles might reflect a high frequency of aneuploidy related to ovarian stimulation (7). However, in this case results from karyotype analyses of the fetuses in both pregnancies were normal.…”
Section: Discussionmentioning
confidence: 53%
“…Many cytogenetic studies in human oocytes have been reported (Martin et al 1986;Plachot et al 1987;Veiga et al 1987;Wramsby et al 1987;Bongso et al 1988;Pellestor and Sele 1988;Van Blerkom and Henry 1988;Ma et al 1989;Papadopolous et al 1989;Pieters et al 1989) and, although hyperhaploidy has often been recorded, there has been no unequivocal photographic evidence of hyperhaploid meiosis II metaphases with 24 clear whole chromosomes or with single chromatids. However, Martin et al (1986) looked at the meiosis II chromosomes of 50 freshly aspirated uninseminated oocytes and described one with a count of 23 in which one chromosome number 3 was represented as a single chromatid.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method of calculating aneuploidy ignores the contribution made by anaphase lag leading to loss of material. Van Blerkom and Henry (1988) observed chromosomes scattered in the cytoplasm of freshly ovulated and failed to fertilise oocytes that were not associated with the metaphase spindle in 2.6 % of cases. A FISH study was conducted by Anahory et al (2003) using double label (site specific and whole chromosome paint) probes for a similar range of chromosomes to the above, with the omission of chromosomes 1 and 12.…”
Section: The Aneuploidy Rate In Human Oocytesmentioning
confidence: 97%